Um estudo dos perfis estratégicos das empresas pertencentes ao cluster de automação e controle do RS considerando suas capacidades estratégicas, as incertezas ambientais percebidas pelos gestores e seu desempenho organizacional - Candia, Paulo Fernando de Lucca (Universidade do Vale do Rio dos Sinos, 2016)
This research consists of a cross-sectional study with descriptive nature applied to the cluster Automação e Controle RS. Its goal is to analyze whether the strategic typology developed by Desarbo et al. (2005) is able to differentiate adaptation strategies in the companies which are part of the sample, as well as understand the relationship among strategic capabilities, environmental uncertainties and firm performance from the perspective of strategic management. Thru a quantitative approach, this study used the framework proposed by Desarbo et al. (2005) with some additions and adaptations suggested by the author. The data collected were organized and submitted to a set of statistical procedures - including descriptive statistic, cluster analysis, ANOVA and correlation and regression analysis - in order to test and validate the hypotheses investigated. It was possible to identify differences in the strategic adjustment processes in the cluster. However, no significant correlation among strategic capabilities, uncertainties and organizational performance was revealed. Because of this, no predictive model that explained the variation in the organizational performance (dependent variable) by varying the levels of strategic capabilities and environmental uncertainties (independent variables) was suggested.
Keywords: Adaptação estratégica; Capacidades estratégicas; Incerteza ambiental; Desempenho organizacional; Strategic adaptation; Strategic capabilities; Environmental uncertainty; Business performance; ACCNPQ::Ciências Sociais Aplicadas::Administração